2020
DOI: 10.1108/jaoc-05-2020-0063
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to change in the financial management of small family-owned firms: a grounded theory of family firms in Laos

Abstract: Purpose The purpose of this study is to apply a grounded theory (GT) approach to develop a theory of resistance to change in the financial management of Laotian family firms. Design/methodology/approach The research adopts a GT approach, using a theoretical sampling procedure. Interviews were conducted with 36 Laotian family firms between April 2017 and May 2019. The in-depth interview transcriptions were analyed using open coding, axial coding and selective coding. Findings The interviewees identified tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…Our finding shows that financial capital continues to be a major factor determined by income, investments, savings and loans due to high competition. These findings are consistent with earlier studies on entrepreneurial families (Dunn and Holtz-Eakin, 2000; Kim et al , 2006; Coleman, 2007; Mari et al , 2016; Daovisan and Shen, 2020; Daovisan and Chamaratana, 2020a, b), leading to the implication that high financial capital may create a sustainable competitive advantage. Saad et al (2018) and Gomez-Mejia et al (2018) found that growing the financial capital, which is positively associated with working capital, has become an increasingly important and fundamental aspect of competition.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our finding shows that financial capital continues to be a major factor determined by income, investments, savings and loans due to high competition. These findings are consistent with earlier studies on entrepreneurial families (Dunn and Holtz-Eakin, 2000; Kim et al , 2006; Coleman, 2007; Mari et al , 2016; Daovisan and Shen, 2020; Daovisan and Chamaratana, 2020a, b), leading to the implication that high financial capital may create a sustainable competitive advantage. Saad et al (2018) and Gomez-Mejia et al (2018) found that growing the financial capital, which is positively associated with working capital, has become an increasingly important and fundamental aspect of competition.…”
Section: Discussionsupporting
confidence: 92%
“…According to Peteraf and Barney (2003), competitive advantage creates “economic value” and “firm performance” for capable and efficient competitors. Therefore, our study focusses on the “economic values” of capital accumulation for the competitive advantage of entrepreneurial families (Orhangazi, 2008; Sigalas et al , 2013; Daovisan and Chamaratana, 2020a, b).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations